Neonatal enteric duplication cyst with segmental gut volvulus - Syed Waqas Ali; Nayha Fatima; Sidra Amir; Muhammad Hamayl Zeeshan; Muhammad Arif Mateen (Elsevier, 2021)
Enteric duplication cyst (EDC) in a neonate with volvulus of small bowel is an extremely rare clinical condition that can present symptomatically with abdominal distention, bilious vomiting and abdominal pain. We present a case of jejunal EDC associated with jejuno-ileal volvulus in a 3-day old neonate, where we highlight the importance of early management on suspicion of volvulus to prevent complications.